Effect of increased protein intake and exogenous ketosis on body composition, energy expenditure and exercise capacity during a hypocaloric diet in recreational female athletes - Hiroux, Charlotte; Schouten, Moniek; de Glisezinski, Isabelle; Simon, Chantal; Crampes, François; Hespel, Peter; Koppo, Katrien (Frontiers in Physiology, 2023)
Introduction: Since low body weight is an important determinant of success in many sports such as gymnastics, martial arts and figure skating, athletes can benefit from effective weight loss strategies that preserve muscle mass and athletic performance. The present study investigates the effects of increased protein intake and exogenous ketosis on body composition, energy expenditure, exercise capacity, and perceptions of appetite and well-being during a hypocaloric diet in females. Methods: Thirty-two female recreational athletes (age: 22.2 ± .5 years; body weight: 58.3 ± .8 kg; BMI: 20.8 ± .2 kg·m−2) underwent 4 weeks of 30% caloric restriction and were randomized to receive either an increased daily amount of dietary protein (PROT, ∼2.0–2.2 g protein·kg−1·day−1), 3 × 20 g·day−1 of a ketone ester (KE), or an isocaloric placebo (PLA). Body composition was measured by DXA, resting energy expenditure (REE) by indirect calorimetry, exercise capacity during a VO2max test, appetite hormones were measured in serum, and perceptions of general well-being were evaluated via questionnaires. Results: The hypocaloric diet reduced body weight by 3.8 ± .3 kg in PLA, 3.2 ± .3 kg in KE and 2.4 ± .2 kg in PROT (Ptime<.0001). The drop in fat mass was similar between treatments (average: 2.6 ± .1 kg, Ptime<.0001), while muscle mass was only reduced in PLA and KE (average: .8 ± .2 kg, Ptime<.05), and remained preserved in PROT (Pinteraction<.01). REE [adjusted for lean mass] was reduced after caloric restriction in PLA (pre: 32.7 ± .5, post: 28.5 ± .6 kcal·day−1·kg−1) and PROT (pre: 32.9 ± 1.0, post: 28.4 ± 1.0 kcal·day−1·kg−1), but not in KE (pre: 31.8 ± .9, post: 30.4 ± .8 kcal·day−1·kg−1) (Pinteraction<.005). Furthermore, time to exhaustion during the VO2max test decreased in PLA (by 2.5 ± .7%, p < .05) but not in KE and PROT (Pinteraction<.05). Lastly, the perception of overall stress increased in PLA and PROT (p < .05), but not in KE (Pinteraction<.05). Conclusion: Increased protein intake effectively prevented muscle wasting and maintained exercise capacity during a period of caloric restriction in female recreational athletes. Furthermore, exogenous ketosis did not affect body composition, but showed its potential in weight management by preserving a drop in exercise capacity and REE and by improving overall stress parameters during a period of caloric restriction.